2000
DOI: 10.1021/om000734k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Reactivity of M(allyl)3 (M = Rh, Ir) with Donor Ligands

Abstract: Reactions of M(allyl) 3 [M ) Rh, Ir] with a variety of donor ligands have been investigated. While both complexes are unreactive toward "hard" N-and O-donor ligands, "soft" ligands such as tolylisothiocyanate, tertiary phosphines, CO, and aryl isocyanides are readily added. Whereas ligand additions to Rh(allyl) 3 are often accompanied by reduction of the Rh(III) center, analogous reactions with Ir(allyl) 3 afford stable trivalent products containing σ-allyl ligands. The molecular structures of several derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…It has also been shown that the bulky ligand substituents can cause modifications to the structure and solution behaviour of the stable allylic metal complexes [6]. The reactivity of rhodium and iridium allylic complexes with various substrates as reactants has been reported [7]. The catalytic asymmetric hydrogenation of a-functionalized ketones using chiral Ru(II)-allyl complexes has also been reported [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the bulky ligand substituents can cause modifications to the structure and solution behaviour of the stable allylic metal complexes [6]. The reactivity of rhodium and iridium allylic complexes with various substrates as reactants has been reported [7]. The catalytic asymmetric hydrogenation of a-functionalized ketones using chiral Ru(II)-allyl complexes has also been reported [8].…”
Section: Introductionmentioning
confidence: 99%
“…With the aim of continuing this effort, we report herein the use of a different functionalized benzyl carbene chelate ligand and its coordination to a different iridium source reagent, namely [IrCl 3 (tht) 3 ] (tht = tetrahydrothiophene), [11] which is soluble in non-polar organic solvents. This change of reagents allows the preparation of blue-emitting Ir III complexes in a two-step synthetic manipulation involving: 1) generation of the cationic silver carbene intermediate, [12] and 2) carbene transfer [13] to the Ir III center and cyclometalation, followed by addition of the third, pyridyl azolate chelate ligand.…”
mentioning
confidence: 99%
“…This concept has proved to be successful for the synthesis of a series of phosphorescent Ir III complexes. [10] Unfortunately, due to the twisting motion of the chelate ligands, which facilitates the nonradiative decay channels, these complexes do not serve as efficient true-blue phosphors but instead have been applied as the host materials for green phosphorescent OLEDs.With the aim of continuing this effort, we report herein the use of a different functionalized benzyl carbene chelate ligand and its coordination to a different iridium source reagent, namely [IrCl 3 (tht) 3 ] (tht = tetrahydrothiophene), [11] which is soluble in non-polar organic solvents. This change of reagents allows the preparation of blue-emitting Ir III complexes in a two-step synthetic manipulation involving: 1) generation of the cationic silver carbene intermediate, [12] and 2) carbene transfer [13] to the Ir III center and cyclometalation, followed by addition of the third, pyridyl azolate chelate ligand.…”
mentioning
confidence: 99%
“…With the aim of continuing this effort, we report herein the use of a different functionalized benzyl carbene chelate ligand and its coordination to a different iridium source reagent, namely [IrCl 3 (tht) 3 ] (tht=tetrahydrothiophene),11 which is soluble in non‐polar organic solvents. This change of reagents allows the preparation of blue‐emitting Ir III complexes in a two‐step synthetic manipulation involving: 1) generation of the cationic silver carbene intermediate,12 and 2) carbene transfer13 to the Ir III center and cyclometalation, followed by addition of the third, pyridyl azolate chelate ligand 14.…”
Section: Methodsmentioning
confidence: 99%